International Financial Markets - Lees, Francis A. (New York : Praeger Publishers, 1975)
The book provides a historical, factual, and conceptual framework within which the national and international financial markets function and operate.
Includes bibliographical references
osc 30/8/17
Loans
Keywords: Financial Markets; International Financial Markets